Regulatory and Legal Ways to Resolve Existing Conflicts in the Field of Cyber Security in the Context of the Creation of Cyber Forces of the Armed Forces of Ukraine - Zhyvylo, Yevhen; Dokil, Valentyn (Theory and Practice of Public Administration, 2024)
The current proliferation and commercialization of cyber attack tools has changed the balance of power in cyberspace and allowed a wide range of actors to use cyber tools for geopolitical influence and economic gain. The applicable tools, which can be freely used, provide unprecedented opportunities for espionage, fraud and hacking, the use of which is aimed at financial gain, disruption of the sustainable functioning of critical infrastructure facilities and various forms of ownership of electronic communication systems and networks. The dynamics of the current situation regarding the ability to buy ready-made hardware and software solutions and create individual cyber tools continues to “challenge” national security, the commercial sector and the civilian population. By increasing the ability to acquire cyber tools on a commercial basis, both state and non-state actors can quickly move from new threats to existing ones, so this leap is seen as a key factor in the cyber defense landscape. In the future, this can lead to a high level of geopolitical instability in conflicts that will be more difficult to predict than traditional military changes in the balance of power.Under these conditions, an important task for Ukraine is to create conditions for protecting sovereignty and ensuring the defense capability of the state in cyberspace by supporting the capabilities of the defense forces to carry out active cyber protection of its own information infrastructure and preparing the state to repel military aggression in cyberspace both in peacetime and in a state of war (a special period ). In view of the above, this paper analyzes the current regulatory legal acts of the state regarding the implementation of relevant tasks by cyber security entities within the framework of state cyber defense and national cyber defense measures with the aim of delimiting powers, establishing responsibility for specific areas of activity and implementing priority tasks in this field.